The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2196/14166
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Agents in the Treatment of Mental Health Problems: Mixed-Method Systematic Review

Abstract: BackgroundThe use of conversational agent interventions (including chatbots and robots) in mental health is growing at a fast pace. Recent existing reviews have focused exclusively on a subset of embodied conversational agent interventions despite other modalities aiming to achieve the common goal of improved mental health.ObjectiveThis study aimed to review the use of conversational agent interventions in the treatment of mental health problems.MethodsWe performed a systematic search using relevant databases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
151
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(168 citation statements)
references
References 41 publications
15
151
0
2
Order By: Relevance
“…30,31 Notably, MYLO's therapeutic approach (curious questioning using MOL) is exclusively concerned with enabling the client to develop their own understanding of the problem to gain new insights and solutions, which is rather different to other relational agent interventions that have a greater focus on psychoeducation, advice giving, or teaching/learning new skills. [56][57][58] Our findings are also consistent with research indicating that maximizing the opportunity to talk freely is important for users, e.g., through enabling free text input and tailoring the session content or duration of sessions. 58 Repetitive, confusing or inappropriate questions, which highlighted MYLO's lack of understanding, were associated with a loss of faith in the MYLO intervention and were identified as unhelpful.…”
Section: Main Findingssupporting
confidence: 86%
See 2 more Smart Citations
“…30,31 Notably, MYLO's therapeutic approach (curious questioning using MOL) is exclusively concerned with enabling the client to develop their own understanding of the problem to gain new insights and solutions, which is rather different to other relational agent interventions that have a greater focus on psychoeducation, advice giving, or teaching/learning new skills. [56][57][58] Our findings are also consistent with research indicating that maximizing the opportunity to talk freely is important for users, e.g., through enabling free text input and tailoring the session content or duration of sessions. 58 Repetitive, confusing or inappropriate questions, which highlighted MYLO's lack of understanding, were associated with a loss of faith in the MYLO intervention and were identified as unhelpful.…”
Section: Main Findingssupporting
confidence: 86%
“…[56][57][58] Our findings are also consistent with research indicating that maximizing the opportunity to talk freely is important for users, e.g., through enabling free text input and tailoring the session content or duration of sessions. 58 Repetitive, confusing or inappropriate questions, which highlighted MYLO's lack of understanding, were associated with a loss of faith in the MYLO intervention and were identified as unhelpful. These themes are consistent with studies of other relational agent interventions [56][57][58][59][60][61] and are perhaps not unique to MYLO.…”
Section: Main Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…They suggest that there is a great deal of clinical potential in using AI in this manner. In a review of the literature from 1946 to 2018 on conversational agents used in the treatment of mental health problems, Gaffney et al ( 2019 ) found only 13 qualifying studies out of an initial 30,853 with four being what they called full-scale RCTs. They concluded that the use of conversational agents was limited but growing.…”
Section: Ai and The Future Of Mental Health Servicesmentioning
confidence: 99%
“…Preliminary evidence suggests that ECAs are perceived to be less judgmental, less intimidating, and more likable than a human counterpart, resulting in participants feeling less guilty and more motivated by the interaction [ 13 , 14 , 17 , 18 ]. Collectively, this evidence suggests that ECAs may be effective in providing support for chronic disease management as they help to engage users by building a social and emotional relationship over time [ 9 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%